Prospects For Using Socio-Cultural Technologies To Enhance The Aesthetic Thinking Of Youth In The Process Of Spiritual Renewal Of Society (Texas Journal of Philology, Culture and History, 2025)
This article analyzes the pressing issues of developing the aesthetic thinking of youth within the process of spiritual renewal of society from a philosophical and aesthetic perspective. In particular, the role, impact, and prospects of modern socio-cultural technologies in this process are examined in depth. Aesthetic thinking is not only the ability to perceive and appreciate beauty but also a powerful means of nurturing the inner world of an individual and spiritually awakening them.